The Attalids of Pergamon and Anatolia - Kaye, Noah, 1981- (Cambridge, United Kingdom ; New York, NY)
xviii, 444 sayfa
Keywords: “In the sunny, austere central hall of the Pergamon Museum in Berlin, wrapping around the room's walls like a serpent, then rising halfway to the ceiling on marble steps, stands a strident, if also fragmentary statement of empire. It is an unfinished wedding cake of a building. Tourists recline languidly on its ascent, like guests with nowhere to sit. The room is just too small; it is overtaken by the object on display ̣- The Great Altar of Pergamon. The Altar, with its two sculptural friezes, the outer, depicting the Battle of Gods and Giants, the inner, the tale of Telephos, son of Herakles and heroic ancestor of the Attalid dynasty, was discovered in 1871, the year in which the Second German Empire was born. The engineer Karl Humann stumbled upon the marble fragments while building infrastructure for Ottoman Turkey, making the Altar as we know it a pure product of German, French and British competition for influence in the Middle East. Today, Turkey has regained confidence, and officials from the Prussian Cultural Heritage Foundation expect Ankara to ask for it back” --